Spinnen aus Malaisefallen - Broen, Bodo von (Arachnologische Mitteilungen, 1994)

(untitled)
The spider fauna of the higher vegetation strata is by far less well investigated than the bulk of epigeic spiders. The present paper refers to spiders collected in Malaise traps that were used during an insect sampling program in Brandenburg (Germany) in 1992-1993. In spite of a rather unusual sampling technique for spiders, the species report presented might add to our knowledge useful data on arboricolous spiders.